COMPARISON OF COPPER LEVEL AND COLOR VISION IN PULMONARY TUBERCULOSIS PATIENTS BEFORE AND AFTER ETHAMBUTOL TREATMENT IN CATEGORY I AND II - Devi Azri Wahyuni; Febria Restissa; Ahmad Rasyid; Erial Bahar (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Copper as a metal chelator in ethambutol may interfere oxidative phosphorylation and mitochondrial function that are useful in the formation of ATP, so that long-term damage can cause apoptosis and interfere color vision. This study aims to determine the correlation between duration of ethambutol and copper levels in serum with color vision disorder examined with Farnsworth Munsell 100 Hue (FM100) in patients with tuberculosis. This study was an explorative observation of 20 samples during November 2017 - January 2018 period. Comparative analysis using independent t-test, paired t-test, Wilcoxon test and Mann-Whitney test, while correlation analysis using Spearman's test and Pearson's test. There was a significant difference of FM100value before and after in category I (p=0.000) with increase of total error value 11.80+5.31 or category II (p=0.000) with increase of total error value 15.00+7.41. There was significant difference of Cu2+ level before and after in category I (p=0.005) with decrease of Cu2+ level 15.57+5.04 mg/dL or category II (p=0.005) with decrease of Cu2+ level 31.66+7.35 mg/dL. The duration of Ethambutol was related to changes in color vision examined with FM100.